Psychosocial intervention for schizophrenia. Issue 1 (31st December 2023) - Sun, Xiaoying; Yue, Suping; Duan, Mingjun; Yao, Dezhong; Luo, Cheng
Abstract: Schizophrenia is a serious mental illness. The main treatment of schizophrenia is antipsychotic medications. Meanwhile, psychosocial treatment can be incorporated to improve the efficacy of treatment, including cognitive behavioral therapy, cognitive remediation therapy, family therapy, psychoeducation, social skill training, and vocational rehabilitation. This study aimed to summarize the efficacy of various psychosocial interventions for schizophrenia through a literature review. The literature search was conducted by using the keywords "schizophrenia" and "psychosocial intervention, " "cognitive remediation therapy" "cognitive behavior therapy, " "family intervention, " "psychoeducation, " "social skill training" or "vocational rehabilitation" on PubMed, CENTRAL, Wiley Online Library and Web of Science. Psychosocial intervention can further improve the symptoms and functioning of patients, enhance drug compliance, reduce the recurrence and readmission rates, and increase the employment rate when added to treatment as usual.